دور القطاع الزراعي في الاختلالات الهيكلية في الاقتصاد العراقي خلال المدة - احمد, محسن ابراهيم (Sulaimani Journal for Humanities, 2003)
Iraq's economy, like any other underdeveloped country that depends on agricultural production and mining, is suffering from a number of problems and various big crises, above all, imblanace in the economical structure. This is the outcome of its economy, which is split into two halfes. The first half is a large broad underdeveloped sector that embodies a high percent of manpower in the countrey, but participates, with alow percent, in the formation of the local income. The second half is a small progressed sector that embodies a low percent of manpower, but highly particpates in the formation of the local public income. To adjust that Imbalanced economical condition, Iraq has started, since the early sixties of the 20th century, to follow some economical procedures through economical plans to increase the participation of the goods production sectors, especially the industrial sector in the formation of local general income aiming at varying the economical structure, and then balancing it. However, throughout this research it has been found out that Iraq, in spite of all its humanitarian and materialistic capacities could not achieve its goals. It even deepened and consolidated its economical imblanaced structure through abundant investment in the services and industrial sectors, and ignoring the agricultural sector, which led to an increase in the Imbalance in the agricultural structure. This had great negative effect on all the other economical sectors, especially the inflation and expansion by embodying he maximal percent of manpower, most of which are inexperienced workers. This does not match with the economica growth stage in Iraq. Thus, it deepened the imbalance of Iraq's economical structure.